2013
DOI: 10.1073/pnas.1217399110
|View full text |Cite
|
Sign up to set email alerts
|

Murine leukemia virus glycosylated Gag blocks apolipoprotein B editing complex 3 and cytosolic sensor access to the reverse transcription complex

Abstract: Pathogenic retroviruses have evolved multiple means for evading host restriction factors such as apolipoprotein B editing complex (APOBEC3) proteins. Here, we show that murine leukemia virus (MLV) has a unique means of counteracting APOBEC3 and other cytosolic sensors of viral nucleic acid. Using virus isolated from infected WT and APOBEC3 KO mice, we demonstrate that the MLV glycosylated Gag protein (glyco-Gag) enhances viral core stability. Moreover, in vitro endogenous reverse transcription reactions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
197
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(208 citation statements)
references
References 54 publications
(74 reference statements)
11
197
0
Order By: Relevance
“…NSG mice lack cells of the adaptive immune system (B-, T-and NK-cells) and have several defects in classic innate functions, including an absent hemolytic complement system, reduced dendritic cell function, and defective macrophage activity (10). Our study also demonstrated that E-MuLV replication is not blocked by the Fv1 restriction factor, which is the most common and powerful restriction against MuLV in the murine system at the intracellular level (18); nor has the Emv30 provirus been subject to incapacitating mutations, reflecting its relatively new insertion into the NOD germ line and the low impact of APOCBEC3 restriction on this class of MuLVs (29). Thus, NOD mice differ strikingly from the common inbred mouse strains DBA/2, BALB/c, and B6, in which the eERV provirus is replication incompetent, restricted by the Fv1 factor, or both, respectively.…”
Section: Discussionmentioning
confidence: 71%
“…NSG mice lack cells of the adaptive immune system (B-, T-and NK-cells) and have several defects in classic innate functions, including an absent hemolytic complement system, reduced dendritic cell function, and defective macrophage activity (10). Our study also demonstrated that E-MuLV replication is not blocked by the Fv1 restriction factor, which is the most common and powerful restriction against MuLV in the murine system at the intracellular level (18); nor has the Emv30 provirus been subject to incapacitating mutations, reflecting its relatively new insertion into the NOD germ line and the low impact of APOCBEC3 restriction on this class of MuLVs (29). Thus, NOD mice differ strikingly from the common inbred mouse strains DBA/2, BALB/c, and B6, in which the eERV provirus is replication incompetent, restricted by the Fv1 factor, or both, respectively.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, perhaps the structure of MLV particles limits the interconversion of these hypothetical forms of mA3. Recent evidence indicates that the glyco-Gag of MLV affects virus structure in a way that interferes with mA3 action (43,44). In any case, further work will be required to elucidate the mechanisms of mA3 restriction of MLV and of the resistance of MLV to mA3-induced hypermutation.…”
Section: Figmentioning
confidence: 99%
“…However, M-MLV becomes much more sensitive to restriction by mA3 when expression of the glycosylated viral Pr80 Gag (gPr80) protein is suppressed (15,18). This is reportedly caused by gPr80 blocking access of mA3 to the reverse transcription complex in viral cores (15).…”
mentioning
confidence: 99%
“…The most striking example is the Moloney MLV (M-MLV) gammaretrovirus, which is modestly restricted by mA3 in the absence of detectable G-to-A hypermutation, despite efficiently packaging mA3 into virions (33,(36)(37)(38)(39)(40). However, M-MLV becomes much more sensitive to restriction by mA3 when expression of the glycosylated viral Pr80 Gag (gPr80) protein is suppressed (15,18). This is reportedly caused by gPr80 blocking access of mA3 to the reverse transcription complex in viral cores (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation